2020
DOI: 10.1049/pel2.12030
|View full text |Cite
|
Sign up to set email alerts
|

First self‐resonant frequency of power inductors based on approximated corrected stray capacitances

Abstract: Inductive devices are extensively employed in power electronic systems due to their magnetic energy storage and power transfer capabilities. The current trend is towards increasing the frequency of operation in order to reduce the size of the magnetic components, but the main drawback is that the parasitic capacitance effect can become significant, and degrade the performance of the system. This work analyses the influence of this stray capacitance, and considers how to improve the performance of the device. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…Other important manufacturing details can be observed: there are no separate resonant capacitors ( Figure 7 b), and the dielectric materials of all four PCB pancake plates form an internal resonant capacitor together with the flat spiral coils as capacitor plates. Considering that the standard plate thickness is 1.5 mm, the relative dielectric constant of FR4 fiberglass epoxy resin is 3.7–4, and the turn spacing or copper layer is almost double the plate thickness, only the 250–270 pF capacitance between the two copper spirals is relevant [ 39 ]. Another small internal capacitance difference of 20 pF can appear due to copper layer misalignment and turn spacing, but it does not significantly affect the resonant frequency of 1.53–1.58 MHz.…”
Section: Resultsmentioning
confidence: 99%
“…Other important manufacturing details can be observed: there are no separate resonant capacitors ( Figure 7 b), and the dielectric materials of all four PCB pancake plates form an internal resonant capacitor together with the flat spiral coils as capacitor plates. Considering that the standard plate thickness is 1.5 mm, the relative dielectric constant of FR4 fiberglass epoxy resin is 3.7–4, and the turn spacing or copper layer is almost double the plate thickness, only the 250–270 pF capacitance between the two copper spirals is relevant [ 39 ]. Another small internal capacitance difference of 20 pF can appear due to copper layer misalignment and turn spacing, but it does not significantly affect the resonant frequency of 1.53–1.58 MHz.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the parasitic capacitor causes self-resonance of the inductor, which is the resonance between the inductor and the parasitic capacitor [10]. The frequency at which the self-resonance forms is called the self-resonance frequency (SRF), which is dependent on the inductor geometric parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the SRF based on simple analysis. Lope et al [10] analyzed the first SRF of planar inductors with a simple circuit model. Findley et al [11] developed the differential inductor having high SRF based on a simple SRF analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive components are essential in power electronics converters [1], [2]. For the converters utilizing wide-bandgap devices [3], [4], the parasitic capacitance in magnetic components, including inductors [5], [6], transformers [7] and motors [8], is of significant importance due to the fast switching characteristics (high dv/dt value) of the wide-bandgap devices [8], [9]. It is reported that such parasitic capacitance can significantly contribute to the capacitive current during the switching transients [10] and may result in increased conducted noise and extra switching losses dissipated by the transistors [11]- [14].…”
Section: Introductionmentioning
confidence: 99%